The Application of Deep Learning in Fiqh Education: Creating Humanistic and Relevant Learning in The Digital Age - Azis, Abdul; Asysyifa, Fitra; Sein, Lau Han; Khulasoh, Siti (Universitas Muhammadiyah Surakarta, 2025)
Teachers in fiqh education, in particular, still use a teacher-centered approach, where the teacher is the main figure in the teaching process. With this method, they rely solely on lectures and memorization as the dominant techniques. Several madrasah ibtidaiyyah teachers indicated that 72% of teachers only emphasize the cognitive aspect without involving deep meaning or value reflection. The research method used in this study is a qualitative approach with library research. Secondary data was obtained from various valid and relevant scientific literature, such as books on Islamic education theory, pedagogy, and reputable journal articles related to deep learning, fiqh education, and humanistic education. Data collection techniques involved identifying literature sources based on their relevance to the topic of fiqh education, while data analysis techniques used the Miles and Huberman method, which involves three stages: data reduction, data display, and drawing conclusions. The results of this study indicate that fiqh education through the deep learning approach emphasizes education that humanizes humanity. Through a deep learning approach, Islamic law is conveyed in a dialogical, inclusive, and tolerant manner, in accordance with the values of maqasid al-syari'ah and rahmatan lil-'alamin. Thus, the integration of deep learning in fiqh education can create a humanistic and relevant learning experience in the digital age. As the urgent need for fiqh education is to build an adaptive, critical, and humanistic Islamic education rooted in humanitarian values. Through this strategy, fiqh is not merely a subject to be memorized but also a source of ethics, spirituality, and policy that is alive in today's digital reality.